Microstructural stability and mechanical properties of Al2O3/Kovar 4 J34 joint vacuum brazed using Ag-5Cu-1Al-1.25Ti (wt%) filler metal. (December 2021) - Wang, J.L.; Yang, Z.W.; Wang, Y.; Wang, D.P.; Li, H.J.
Abstract: The Al2 O3 ceramic and Kovar 4 J34 alloy were effectively bonded by vacuum brazing by using an Ag-based filler metal with a composition of Ag-5Cu-1Al-1.25Ti (wt%). The typical interfacial structure of the Al2 O3 /Kovar 4 J34 joint brazed at 960 °C for 10 min was determined as Al2 O3 /Ti3 (Cu, Al)3 O/Ag(s, s) + Cu(s, s) + disperse AlCu2 Ti/Ti2 Ni + TiFe2 /Kovar. The brazing parameters were observed to have a decisive effect on the microstructure evolution and variation of the mechanical properties of the Al2 O3 /Kovar 4 J34 brazed joints. The maximum shear strength of the brazed joints could reach 150 MPa, and the failure primarily occurred in the ceramic substrate and Ti3 (Cu, Al)3 O reaction layer. Moreover, the microstructural stability of the Al2 O3 /Kovar 4 J34 brazed joints at elevated temperatures was also investigated. After thermal cycling at 600 °C for 3 h, the interfacial structure of the brazed joint did not change obviously except for the thickening of the reaction layer, and the joint shear strength remained at 130 MPa. However, the average shear strength of the joint under the testing temperature of 600 °C was reduced to 73 MPa, and the fracture propagated along the Ag matrix of the brazing seam due to the softening of silver. Highlights: The wetting mechanism of the Al2 O3 /Ag-Cu-Al-Ti system was studied. The typical interfacial structure of the Al2 O3 /Kovar 4 J34 brazed joint was characterized. The microstructural stability and mechanical properties of the joints after high-temperature cycles were investigated.